PROCESS OF PROSPEROUS RESEARCH FILES IN THE CASE DETERMINING NEW INSTITUTIONS IN CRIMINAL MEASURES CORRUPTION - Herlambang Herlambang; Antory Royan; Samhori Samhori (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
This thesis is the result of research on "Process Attorney Researcher Case file in Determine Suspect New on Corruption", specifically this thesis discusses the process of determining the new suspects by prosecutors investigators file corruption cases and factor inhibitors for Attorney Researcher Files Case to determine a suspect new in the case file corruption. In particular, this thesis examines several cases of corruption filed by Investigator Police Resort Arga Makmur District Attorney of Public Prosecutions to Arga Makmur. The results of the study illustrate that the Attorney Researcher in determining new suspects in the case files submitted by police investigators are using the instrument giving direct instructions by the prosecution team of researchers P 19 and the instrument exposes / his case subsequently prosecutors investigators case file gives instructions to the investigator to be fulfilled within 14 days after prosecutors clue investigators met by investigators, the case file is declared complete by prosecutors investigators (P21).